High knee valgus in female subjects does not yield higher knee translations during drop landings: A biplane fluoroscopic study - Torry, Michael R.; Shelburne, Kevin B.; Myers, Casey; Giphart, J. Erik; Pennington, W. Wesley; Krong, Jacob P.; Peterson, Daniel S.; Steadman, J. Richard; Woo, Savio L.-Y. (Journal of orthopaedic research, 2013)
The goal of this study was to determine the effects of peak knee valgus angle and peak knee abductor moment on the anterior, medial, and lateral tibial translations (ATT, MTT, LTT) in the “at risk” female knee during drop landing. Fifteen female subjects performed drop landings from 40 cm. Three‐dimension knee motion was simultaneously recorded using a high speed, biplane fluoroscopy system, and a video‐based motion analysis system. Valgus knee angles and knee abduction moments were stratified into low, intermediate, and high groups and peak ATT, MTT, and LTT were compared between these groups with ANOVA (α = 0.05). Significant differences were observed between stratified groups in peak knee valgus angle (p < 0.0001) and peak knee abduction moment (p < 0.0001). However, no corresponding differences in peak ATT, LTT, and MTT between groups exhibiting low to high‐peak knee valgus angles (ATT: p = 0.80; LTT: p = 0.25; MTT: p = 0.72); or, in peak ATT (p = 0.61), LTT (p = 0.26) and MTT (p = 0.96) translations when stratified according to low to high knee abduction moments, were found. We conclude that the healthy female knee is tightly regulated with regard to translations even when motion analysis derived knee valgus angles and abduction moments are high. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 257–267, 2013